Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acs.jpca.2c04539
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the Effect of Surfactants on the Hygroscopic Growth of Model Sea Spray Aerosol Particles

Abstract: The cloud condensation nuclei activation of sea spray aerosol (SSA) is tightly linked to the hygroscopic properties of these particles and is defined by their physical and chemical properties. While hygroscopic sea salt in SSA strongly influences particle water uptake, the marine-derived components that make up the organic fraction of SSA constitute a complex mixture, and their effect on hygroscopic growth is unknown. To constrain the effect of organic compounds and specifically surface-active compounds that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…6 also shows the comparison of the atomizer and AEGOR sea spray tank aerosols. Although the Collison atomizer has often been used to generate sea salt aerosol, 62,[66][67][68][69][70] in the marine boundary layer sea spray aerosol is generated by bubble bursting, which is more accurately simulated using a sea spray tank. 31,[71][72][73] For the same water salinity, the PSL-containing particles from the AEGOR tank were slightly smaller than those generated by the atomizer, and thus the expectation is that these dried particles will have smaller coatings.…”
Section: Coating Thickness Of Nanoplastic Aerosolsmentioning
confidence: 99%
“…6 also shows the comparison of the atomizer and AEGOR sea spray tank aerosols. Although the Collison atomizer has often been used to generate sea salt aerosol, 62,[66][67][68][69][70] in the marine boundary layer sea spray aerosol is generated by bubble bursting, which is more accurately simulated using a sea spray tank. 31,[71][72][73] For the same water salinity, the PSL-containing particles from the AEGOR tank were slightly smaller than those generated by the atomizer, and thus the expectation is that these dried particles will have smaller coatings.…”
Section: Coating Thickness Of Nanoplastic Aerosolsmentioning
confidence: 99%
“…Surfactants are organic molecules that reduce the surface tension at the interface of a solution. , Surfactants have been measured in seawater and in marine aerosol particles. , Other studies have observed surfactants in anthropogenic-influenced particles, , ambient urban particles, and biogenic terrestrial particles. , Surfactants can impact particle hygroscopic growth , and their potential to act as cloud condensation nuclei. Recent work has used high-resolution mass spectrometry to identify fatty acids and other surfactants in aerosol particles. , These results can be combined with surface tension measurements to confirm the presence of surfactants …”
Section: Introductionmentioning
confidence: 99%
“… 47 , 48 Other studies have observed surfactants in anthropogenic-influenced particles, 49 , 50 ambient urban particles, 51 and biogenic terrestrial particles. 39 , 52 Surfactants can impact particle hygroscopic growth 53 , 54 and their potential to act as cloud condensation nuclei. 55 57 Recent work has used high-resolution mass spectrometry to identify fatty acids and other surfactants in aerosol particles.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, Knight et al show the remarkable ability to monitor the evolution of the optical properties of a single particle as its composition changes. Other topics covered include a study of the impact of organic surfactants on the hygroscopicity of sea-salt/organic particles and a study showing that particle charge does not impact the photodegradation of oleic acid particles . Lastly, Edwards et al show that important human health-related properties of SOA, the presence of reactive organic species and environmentally persistent free radicals, vary with SOA precursor and the chemical regime in which the SOA is formed.…”
mentioning
confidence: 99%